1996
DOI: 10.3109/07435809609030513
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of exercise at low altitude (350 meters below sea level) on hormones of the anterior pituitary & cortisol in athletes

Abstract: The purpose of this study was to examine the effects of exercise on anterior pituitary hormones (adrenocorticotropic hormone (ACTH), leutinizing hormone (LH) and growth hormone) as well as on cortisol at low altitude (350 meters below the sea level) and to compare these effects with those at a moderate level altitude (620 meters above the sea level). Ten male athletes with running experience participated in a 21-Km competitive race. Serum levels of ACTH, LH, growth hormone and cortisol were measured before and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…On the other hand, exercise at altitudes above sea level has no statistically significant stimulatory effect on plasma ACTH levels. Plasma cortisol levels in athletes were higher following exercise in environments both below and above sea level [1, 2]. It was suggested that the higher barometric pressure and higher temperature of the JV is responsible for this increase in ACTH levels in response to exercise.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, exercise at altitudes above sea level has no statistically significant stimulatory effect on plasma ACTH levels. Plasma cortisol levels in athletes were higher following exercise in environments both below and above sea level [1, 2]. It was suggested that the higher barometric pressure and higher temperature of the JV is responsible for this increase in ACTH levels in response to exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Hormonal homeostasis, carbohydrate and lipid metabolism in people of the Jordan Valley (JV), which is located at 320 m below sea level, were shown to be different from those of people living above sea level [1, 2, 3, 4]. Bashir et al [1]suggested that exercise in trained athletes in the JV increases pituitary secretion of ACTH leading to higher plasma ACTH levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dulac et al found that cortisol concentrations in blood were significantly increased during long-distance swimming in cold water 98) . Serum cortisol level increases in response to exercise at moderated altitude [99][100][101] . Guilland et al observed increased urinary excretion of cortisol during mountaineering between 4,800 and 7,100 m…”
Section: Environmental Effectsmentioning
confidence: 99%
“…It was shown that thermal stress caused increases in cortisol levels [96][97][98][99] . During swimming, the concentrations of cortisol are higher when the environment is hot 98,99) . Dulac et al found that cortisol concentrations in blood were significantly increased during long-distance swimming in cold water 98) .…”
Section: Environmental Effectsmentioning
confidence: 99%